Routing protocols for efficient communication in UAVNETs: A comprehensive review and analysis - Patel, Surabhi; Pathak, Heman (Vietnam Journal of Science and Technology, 2026)
The efficient communication among Unmanned Aerial Vehicles (UAVs) has become crucial due to their rapid development and expanding use in various applications. Unmanned Aerial Vehicle Networks (UAVNETs) are increasingly recognized as an effective way of facilitating cooperative and coordinated operations among UAVs. Nevertheless, the distinctive attributes of UAVs, including their mobility, constrained energy resources and dynamic network topology, present major challenges when it comes to designing efficient routing protocols. This research paper provides a thorough review of routing protocols that are specifically designed for UAVNETs. The objective of this study is to present a comprehensive analysis of the current routing protocols, highlighting their main characteristics and the specific issues they aim to resolve.